Peningkatan Hasil Belajar Matematika melalui Metode Penemuan Terbimbing Berbantuan Media Pembelajaran pada Siswa Kelas IV SDN 14 Turatea - Nada Awalyah Ahmad; Baharullah Baharullah; Hamdana Hadaming (International Forum of Researchers and Lecturers, 2023)
The formulation of the problem in this study is whether the guided discovery method assisted by learning media can improve mathematics learning outcomes in fourth grade students at SDN 14 Turatea. The purpose of this study was to improve mathematics learning outcomes through guided discovery methods assisted by learning media in fourth grade students at SDN 14 Turatea. This type of research is Classroom Action Research (PTK) which is carried out in two cycles. The subjects in this study were 17 grade IV students at SDN 14 Turatea in the 2022-2023 academic year. Research procedures include planning, implementation of action, observation and reflection. The results showed that in the first cycle of students who completed individually only 10 people or 59% and the average score obtained was 69. Meanwhile in the second cycle where out of 17 students there were 14 people or 82.35% had fulfilled the KKM and the average score -the average obtained was 81.76. Based on the results of this study, it was concluded that the application of the guided discovery method assisted by learning media can improve student learning outcomes in class IV SDN 14 Turatea.